P Pelatihan Desain Grafis Bagi Siswa-Siswi SMA negeri 5 Bandar Lampung - ade Moussadecq; Desiana Muryasari; Abdi Darmawan; Iki Nursyanto; Ketut Artaye; Helen Larissa (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Improving graphic design skills for high school students can be organized by the school through extra-curricular activities or external activities between the school and other parties (Sitompul et al., 2022). SMA Negeri 5 Bandar Lampung is one of the state high schools located on Jl. Soekarno-Hatta (By Pass), New Waydadi, Sukarame, Bandar Lampung City. Graphic design training for SMA Negeri 5 Bandar Lampung students aims to provide knowledge and skills in the field of graphic design so that these students can use their abilities to help design flyers, information media, and posters for school activities or even to prepare them to enter the industrial world. after graduating from school. This community service activity is carried out using presentation, discussion, and practicum methods. After the presentation of the introductory material at the beginning of the session by the presenter, the students immediately practiced on their respective computers according to the directions or modules are given by the presenter. The initial stages of design are making pattern sketches, preparing layouts, and choosing colors that match the visual form of the designed graphic design work.